1986
DOI: 10.1111/j.1469-8137.1986.tb02912.x
|View full text |Cite
|
Sign up to set email alerts
|

THE RESPONSE OF SELECTED SALT‐TOLERANT AND NORMAL LINES OF FOUR GRASS SPECIES TO NaCl IN SAND CULTURE

Abstract: SUMMARYAfter 7 weeks' growth in varying NaCI concentrations in sand culture, dry matter production and tiller number were cotnpared for the progenies of NaCl-tolerant selection lines and the progenies of unselected control lines of Holcus lanatus L., Lolium perenne L., Dactylis glomerata L. and Festuca rubra L. The tolerant lines had been produced by selection at the seedling stage. In each species, selected lines produced significantly more dry matter and had greater tiller numbers than unselected material, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 16 publications
(10 reference statements)
4
16
0
Order By: Relevance
“…Troncoso et al (1999a), working with in vitro grapevine rootstocks, also indicated that desiccation as a result of salt excess began in the leaf tissues. This effect on the water content has been indicated as a result of the action of salt on the plant (Greenway and Munns, 1980;Ashraf et al, 1986;Pasternak, 1987;Grattan and Grieve, 1992).…”
Section: Resultsmentioning
confidence: 97%
“…Troncoso et al (1999a), working with in vitro grapevine rootstocks, also indicated that desiccation as a result of salt excess began in the leaf tissues. This effect on the water content has been indicated as a result of the action of salt on the plant (Greenway and Munns, 1980;Ashraf et al, 1986;Pasternak, 1987;Grattan and Grieve, 1992).…”
Section: Resultsmentioning
confidence: 97%
“…It is known that the evolution of a particular character depends mainly on two determinants occurring together for a considerable length of time, i.e., the existence of a great magnitude of appropriate genetic variation and the occurrence of appropriate natural selection (Ashraf et al, 1986;Ashraf, 1994). Geological records suggest that the Salt Range originated during the late Cambrian era remaining terrestrial for the most time since then.…”
Section: Discussionmentioning
confidence: 99%
“…Natural populations can vary dramatically in salt tolerance across distances as little as 10 m (Casler and Duncan, 2003). Salt tolerant genotypes of turfgrasses have an ability to evolve a form of salt dependence, as illustrated by greater increases in root and shoot growth under high-vs. low-saline growth conditions (Ashraf et al, 1986;Grieve et al, 2004). Salt tolerant plants have the ability to minimize these detrimental effects by producing a series of anatomical, morphological and physiological adaptations (Poljakoff-Mayber, 1988), such as an extensive root system and salt secreting glands on the leaf surface (Gorham et al, 1985;Marcum and Murdoch, 1990;Marcum et al, 1998;Sinha et al, 1986) and restricting the uptake of toxic ions (Ashraf, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Greater reduction in root length under salinity stress compared to controlled condition and positive correlation at both genotypic and phenotypic levels with number of tillers/plant, shoot and root dry weights indicated that this trait was strongly associated with salinity tolerance of the plant. Therefore, root length may be poten-tially a good selection criterion under salt stress conditions as reported by Ashraf et al (1986).…”
Section: Discussionmentioning
confidence: 99%